Exceptional learners: an introduction to special education - Hallahan, Daniel (New York: Pearson, 2006)
Contents: Exceptionality and special education. Current frends and issues. Multicultural and bilingual aspects of special education. Parents and families. Learners with mental retardation. Learners with learning disabilities. Learners with attention deficit hyperactivity disorder
Keywords: Educación Especial